AGE AND GENDER FEATURES OF TOOTH LOSS ACROSS THE POPULATION OF KRASNODAR KRAI - A. K. IORDANISHVILI; A. I. VOLODIN; M. I. MUZYKIN; N. V. LAPINA; V. V. SAMSONOV (Кубанский научный медицинский вестник)
Aim. The article presents features of tooth loss in adults, in view of their age, gender and place of residence.Materials and methods. During the dental examination 3329 (1760 men and 1569 women) adults aged 18 to 102, living in urban and rural areas of Krasnodar Krai of the Russian Federation, features of tooth loss, in view of participants’ age, gender and place of residence were studied. Needs in dental prosthetics of adults was also assayed. Results. During the clinical studies age and gender characteristics of tooth loss across urban and rural population of Krasnodar Krai of the Russian Federation were discovered. In all age groups, regardless of place of residence, the tendency to the loss of a greater number of teeth was observed in men. In the elderly, senile age and among long-livers the total tooth loss was more frequent in women.Conclusion. Analysis of tooth loss in adults of different age groups showed that in order to improve dental health of the adult population of towns and villages regardless of their place of residence it is required to improve prevention program which should address not only children and adolescents but also adults, including elder age groups.